Electrooxidation and Development of a Highly Sensitive Electrochemical Probe for Trace Determination of the Steroid 11-Desoxycorticosterone Drug Residues in Water - Wejdan T. Alsaggaf; Mohammad S. El-Shahawi (International Journal of Electrochemistry)
Anabolic-androgenic steroids (AASs), a class of compounds frequently misused by competitors and unfortunately by the general population, have lately attracted international attention. Thus, extraordinary demands for developing low cost, precise, rapid, and facile protocols for detection and/or determination of AAS have arisen. Hence, the current strategy explores for the first time the redox features of 21-hydroxypregn-4-ene-3, 20-dione, namely, 11-desoxycorticosterone (DCS) AA drug steroid at a glassy-carbon electrode (GCE) in a wide pH range (pH 2.0–10.0) by adsorptive differential pulse-anodic stripping voltammetry (DP- ASV) and cyclic voltammetry (CV). At pH 2, DP-ASV and CV at the optimized pH 2–3 displayed an irreversible anodic peak at 0.4 V versus Ag/AgCl electrode. The dependency of the anodic peak current of the CV at 0.4 V at various concentrations and scan rate of the DCS drug was characteristic of an electrode-coupled electron transfer of EE type mechanism. At the optimized parameters, the proposed strategy allowed quantification of DCS in the concentration range 2.5 -13.19 nM (0.83-4.36 ng mL−1) with satisfactory limits of detection (LOD) and quantization (LOQ) of 9.3 × 10−1 nM (3.1 × 10−1 ng mL−1) and 3.1 nM (1.02 ng mL−1), respectively. A relative standard deviation (RSD) of ±3.93% (n = 5) at 4.0 ng mL−1 DCS was achieved. The established probe was fruitfully employed and validated for trace determination of DCS residues in environmental water. The interference of several common diverse species on DCS sensing was insignificant revealing good selectivity. The established probe exhibited good sensitivity, selectivity, precision, and accuracy, short analytical time, and low cost compared with the reported methods, for DCS determination.